Grafia cuvintelor românești în textele latinești ale lui Dimitrie Cantemir - Florentina Nicolae (Revista de Istorie și Teorie Literară)
In this paper we analyze the spelling of the Romanian words used by Dimitrie Cantemir in his Latin historical works, of historical nature. We will consider Incrementorum et decrementorum Aulae Othmannicae libri tres, Historia Moldo-Vlachica, De antiquis et hodiernis Moldaviae nominibus, Descriptio antiqui et hodierni status Moldaviae, Vita Constantini Cantemyrii. The aim of the research is to identify the influences on Romanian spelling of these words, continuing the research undertaken by Academician Gheorghe Mihăilă (2008), in Descriptio Moldaviae, as well as the solutions proposed by Cantemir, especially on the words rarely or never documented in his bibliographical sources. Anthroponyms and names of the places have been discussed in our previous articles. We intend to bring additions and improvements to our research on the Latin works of the Moldavian Prince; we are not very much concerned with the Latinized forms, but especially with the words the author endeavored to keep in their vernacular shapes.